Is our current understanding and management of nocturia allowing improved care? International Consultation on Incontinence‐Research Society 2018. (10th December 2019) - Hervé, Francois; Abrams, Paul; Bower, Wendy; De Wachter, Stefan; Epstein, Matthew; Lombardo, Riccardo; Robinson, Dudley; Tubaro, Andrea; Wein, Alan; Weiss, Jeffrey P.; Everaert, Karel
Abstract: Aims: Nocturia or waking at night, to urinate is a common cause of awakenings and may lead to sleep disturbance, impaired somatic health, impaired quality of life, and increased mortality. The aim of this report is to point out and discuss the aspects and issues that need to be addressed to improve the care of nocturia. Methods: This paper is a report of the presentations and subsequent discussion of a Think Tank session at the annual International Consultation on Incontinence‐Research Society (ICI‐RS) in June 2018 in Bristol. Results and conclusion: Nocturia is a known risk factor for in‐hospital falls. Unfortunately, its assessment in acutely hospitalized (older) people is not the current practice and ward‐based care plans are not tailored to this symptom. A new care pathway for hospitalized patients who have nocturia should be considered. More research into the relation of cardiovascular disorders and nocturnal polyuria (NP) is warranted and management of NP patients may be improved by involving a cardiologist in their management. There is definitely a need for phenotyping nocturia in relation to bladder capacity, filling phase, and emptying phase symptoms and how to treat the different phenotypes. In the near future, smart automated monitoring devices and applications might help us to diagnose and treat nocturia with less efforts.